Multicultural Educational Approach Influence on Student’s Development - G. Minzaripov, Riyaz; V. Fakhrutdinova, Anastasia; V. Mardakhaev, Lev; I. Volenko, Olga; Y. Varlamova, Elena (International Journal of Criminology and Sociology, 2022)
Recognition of the need to prepare a person for integrating into a multicultural society has led to the problem of organizing educational activities, which provide mastering both languages and cultures, cultural awareness and readiness for intercultural communication, based on the interest in foreign culture and identity of a person as a bearer of own national culture. University educational activities aimed at solving the task of developing personal and professional qualities of a student, who acts as a citizen of their state, meets the social needs and requirements. The paper aims at exploring the specific features of educational activities based on language-and-culture content. The paper employs theoretical and comparative analysis of research describing the basic ideas of teaching foreign languages and cultures as well as studies on personal development in multicultural space. The paper identifies the specific features of educational activities, organized on the basis of language-and-culture content to influence a student as a representative of the nation. One of the major findings is that the teacher’s actions are related to the methods used to expose students to foreign culture in the teacher-led and out-of-class activities. The authors describe the organized educational activities which provide language-and-culture content at different stages of foreign language teaching. In sum, the authors conclude that the main characteristics of educational activities – complexity and integrity; relation to the principle of dialogue between cultures – are determined by the purposes of foreign language teaching and culture, and by the tasks of keeping and developing the students’ features.